2006
DOI: 10.1063/1.2398915
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surface passivation on ultrafast carrier dynamics and terahertz radiation generation in GaAs

Abstract: The carrier dynamics of photoexcited electrons in the vicinity of the surface of (NH4)2S-passivated GaAs were studied via terahertz (THz) emission spectroscopy and optical-pump THz-probe spectroscopy. THz emission spectroscopy measurements, coupled with Monte Carlo simulations of THz emission, revealed that the surface electric field of GaAs reverses after passivation. The conductivity of photoexcited electrons was determined via optical-pump THz-probe spectroscopy, and was found to double after passivation. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
74
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 21 publications
2
74
0
1
Order By: Relevance
“…The surface recombination velocity, S, which is 1000 cm/ s in InP, 3,4 is three orders of magnitude larger ͑10 6 cm/ s͒ for GaAs. 5,6 Recent time-resolved pump-probe terahertz spectroscopy showed that the carrier lifetime in bare GaAs wires is approximately 1 ps, consistent with the expected nonradiative lifetime of NR Ϸ d / 2S Ϸ 1.5 ps for a NW diameter of 30 nm and S =10 6 cm/ s. 7 In addition, the low temperature hole mobility in GaAs is an order of magnitude larger than for InP, which results in a diffusion length which is three times larger than for InP; this increases the sensitivity of carriers to defects within the bulk of the NW core. The recombination lifetime in GaAs is also particularly sensitive to bulk defects such as vacancies and arsenic-antisite defects.…”
Section: Nearly Intrinsic Exciton Lifetimes In Single Twin-free Gaas/mentioning
confidence: 99%
“…The surface recombination velocity, S, which is 1000 cm/ s in InP, 3,4 is three orders of magnitude larger ͑10 6 cm/ s͒ for GaAs. 5,6 Recent time-resolved pump-probe terahertz spectroscopy showed that the carrier lifetime in bare GaAs wires is approximately 1 ps, consistent with the expected nonradiative lifetime of NR Ϸ d / 2S Ϸ 1.5 ps for a NW diameter of 30 nm and S =10 6 cm/ s. 7 In addition, the low temperature hole mobility in GaAs is an order of magnitude larger than for InP, which results in a diffusion length which is three times larger than for InP; this increases the sensitivity of carriers to defects within the bulk of the NW core. The recombination lifetime in GaAs is also particularly sensitive to bulk defects such as vacancies and arsenic-antisite defects.…”
Section: Nearly Intrinsic Exciton Lifetimes In Single Twin-free Gaas/mentioning
confidence: 99%
“…However, it was found that surface-passivated (SP) GaAs PCS emitters tend to show a degraded performance over time, which was attributed to the oxidation of the treated surfaces under continued exposure to air [4].…”
mentioning
confidence: 99%
“…3,12 Control of the surface chemistry is therefore essential in order for these objects to be implemented successfully in nanoscale devices. Chemical surface passivation of GaAs surfaces has previously been shown to reduce both the surface trap density 13 and potentially also the surface recombination velocity. 14 The latter has been attributed to a change in surface potential, and a subsequent reduction in the thickness of the surface depletion region.…”
mentioning
confidence: 99%